AKTIVITAS ANTIBAKTERI SENYAWA GOLONGAN TRITERPENOID DARI BIJI PEPAYA (Carica papaya L.) - I M. Sukadana; Sri Rahayu Santi; N. K. Juliarti (Jurnal Kimia (Journal of Chemistry), 2008)
Isolation, identification, and antibacterial activity examination have been conducted for triterpenoidscompounds of carica papaya L. Maseration of 500 g pawpaw seed powder in n-hexane gave 21.66 g extract whichreacts with Liebermann-Buched reagent resulting in colour change (yellow to purple). Column chromatographyseparation of the extract resulted in 0.05 g yellow isolate (F3) which contains aldehyde triterpenoids. Infrared spectraindicated aliphatic –C-H stretching, -CH2 bending, -CH3 bending, and C=O. Ultra violet – visible spectra showedabsorption at 228.5 nm and proad peak at 287.7 nm. Antibacterial axamination showed that 1000 ppm at the isolateinhibits the growth of Escherichia coli and Staphylococcus auerus.